HepG2 cells mount an effective antiviral interferon‐lambda based innate immune response to hepatitis C virus infection. Issue 4 (21st August 2014) - Israelow, Benjamin; Narbus, Christopher M.; Sourisseau, Marion; Evans, Matthew J.
<x xml:space="preserve">Abstract</x> Hepatitis C virus (HCV) exposure leads to persistent life‐long infections characterized by chronic inflammation often developing into cirrhosis and hepatocellular carcinoma. The mechanism by which HCV remains in the liver while inducing an inflammatory and antiviral response remains unclear. Though the innate immune response to HCV in patients seems to be quite active, HCV has been shown in cell culture to employ a diverse array of innate immune antagonists, which suggests that current model systems to study interactions between HCV and the innate immune system are not representative of what happens in vivo. We recently showed that hepatoma‐derived HepG2 cells support the entire HCV life cycle if the liver‐specific microRNA, miR‐122, is expressed along with the entry factor, CD81 (termed HepG2‐HFL cells). We found that there was a striking difference in these cells' ability to sustain HCV infection and spread when compared with Huh‐7 and Huh‐7.5 cells. Additionally, HepG2‐HFL cells exhibited a more robust antiviral response when challenged with other RNA viruses and viral mimetics than Huh‐7 and Huh‐7.5 cells. HCV infection elicited a potent interferon‐lambda (IFN‐λ), IFN‐stimulated gene, and cytokine response in HepG2‐HFL cells, but not in Huh‐7 cells, suggesting that HepG2‐HFL cells more faithfully recapitulate the innate immune response to HCV infection in vivo. Using this model, we found that blocking the retinoic acid‐inducible gene I (RIG‐I)‐like receptor pathway or the IFN‐λ‐signaling pathway promoted HCV infection and spread in HepG2‐HFL cells. Conclusion: HepG2‐HFL cells represent a new system to study the interaction between HCV and the innate immune system, solidifying the importance of IFN‐λ in hepatic response to HCV infection and revealing non‐redundant roles of RIG‐I and melanoma differentiation‐associated protein 5 in HCV recognition and repression of infection. (Hepatology 2014;60:1170–1179)